Math, asked by vicky4095, 1 year ago

How do you solve 4(b+6)=2(b+5)+2?

Answers

Answered by FadedPrince
2

4(b + 6) = 2(b + 5)+2

4b + 24 = 2b + 10 + 2

4b - 2b = 12 - 24

2b = -12

b = -12/2

b = -6

Answered by ItzSmartyYashi
1

\huge{\underline{\mathbb{\red{Answer}}}}

=  > 4(b + 6) = 2(b + 5) + 2

 =  > 4b + 24 = 2b + 10 + 2

 =  > 4b - 2b = 12 - 24

 =  > 2b =  - 12

  =  > b =  \frac{ - 12}{2}

 =  > b =  - 6

______________________________________

\huge{\underline{\underline{\mathfrak{Thank you}}}}

Similar questions